Pengaruh Citra Merek dan Harga terhadap Minat Beli Konsumen pada MDA Collection - Fariz Irchamsyah Reza; Ustadus Sholihin; Taufik Akbar; Edi Murdiyanto (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to determine the effect between the variables Brand Image (X) and Price (X2) on Consumer Purchase Interest (Y) at MDA Collection. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes its analysis on numbers processed by statistical methods. The data collection techniques used are primary data and secondary data. Sample selection using saturated sampling method, the number of samples in the study obtained 40 respondents at MDA Collection. Data analysis using the Statistical Program for Social Science (SPSS). The analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear analysis tests and hypothesis testing. Based on the results of this study, it shows that partially the Brand Image variable (X1) has a significant effect on Consumer Purchase Interest (Y). Partially Price (X2) has a significant effect on Consumer Purchase Interest (Y). Simultaneously Brand Image (X1) and Price (X2) affect Consumer Purchase Interest (Y).